2016
DOI: 10.4174/astr.2016.91.5.226
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of subtotal cholecystectomy performed for difficult cholecystectomy

Abstract: PurposeLaparoscopic subtotal cholecystectomy (LSC) can be an alternative surgical technique for difficult cholecystectomies. Surgeons performing LSC sometimes leave the posterior wall of the gallbladder (GB) to shorten the operation time and avoid liver injury. However, leaving the inflamed posterior GB wall is a major concern. In this study, we evaluated the clinical outcomes of standard laparoscopic cholecystectomy (SLC), LSC, and LSC removing only anterior wall of the GB (LSCA).MethodsWe retrospectively rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 18 publications
1
26
1
6
Order By: Relevance
“…Our study observed gallbladder wall thickness and presence of multiple calculi as risk factor for a laparoscopic subtotal cholecystectomy as seen in the study done by Shin et al [18] This was also in concordance with the study conducted by Randhawa and Pujahari [19] and Lipman et al, [20] predicting the difficulty of laparoscopic cholecystectomy and conversion.…”
Section: Discussionsupporting
confidence: 92%
“…Our study observed gallbladder wall thickness and presence of multiple calculi as risk factor for a laparoscopic subtotal cholecystectomy as seen in the study done by Shin et al [18] This was also in concordance with the study conducted by Randhawa and Pujahari [19] and Lipman et al, [20] predicting the difficulty of laparoscopic cholecystectomy and conversion.…”
Section: Discussionsupporting
confidence: 92%
“…found lower rates of infectious complication when the posterior wall of the GB was left behind. [ 8 ] Subgroup analysis showed that laparoscopic approach had a lower rate of wound infection. Similar findings were confirmed by Elshaer et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] and Shin et al . [ 8 ] Recently, Strasberg et al . divided it into 'fenestrating' and 'reconstituting' types.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have evaluated the feasibility of LSC in cases of difficult gallbladder . The technique now appears to be well established.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic subtotal cholecystectomy (LSC), which avoids hazardous dissection at Calot's triangle, has been recognized as a safe and feasible alternative to conversion to laparotomy in cases of severe cholecystitis or liver cirrhosis . However, the procedure may be associated with an increased risk of residual or recurrent stones in the gallbladder remnant .…”
Section: Introductionmentioning
confidence: 99%